Community profiling of the urinary microbiota: considerations for low-biomass samples. Issue 12 (December 2018) - Karstens, Lisa; Asquith, Mark; Caruso, Vincent; Rosenbaum, James; Fair, Damien; Braun, Jonathan; Gregory, W.; Nardos, Rahel; McWeeney, Shannon
Abstract Many studies have shown that the urinary tract harbours its own microbial community known as the urinary microbiota, which have been implicated in urinary tract disorders. This observation contradicts the long-held notion that urine is a sterile biofluid in the absence of acute infection of the urinary tract. In light of this new discovery, many basic questions that are crucial for understanding the role of the urinary microbiota in human health and disease remain unanswered. Given that the urinary microbiota is an emerging area of study, optimized techniques and protocols to identify microorganisms in the urinary tract are still being established. However, the low microbial biomass and close proximity to higher microbial biomass environments (for example, the vagina) present distinct methodological challenges for microbial community profiling of the urinary microbiota. A clear understanding of the unique technical considerations for obtaining and analysing low microbial biomass samples, as well the influence of key elements of experimental design and computational analysis on downstream interpretation, will improve our ability to interpret and compare results across methods and studies and is relevant for studies profiling the urinary microbiota and other sites of low microbial abundance. The low biomass of the urinary microbiota presents methodological challenges for studying their role in urological diseases. Here, the authors describe methods for urinary microbiota profiling, and discuss important technical considerations for sampling, DNA sequencing, data processing and downstream analysis. Key points Similar to other areas of the human body, the urinary tract and bladder are inhabited by commensal microorganisms that are collectively referred to as the urinary microbiota. The composition of the urinary microbiota has been associated with response to treatments, risk of infection and urological disorders. Studying the urinary microbiota presents many challenges owing to its low microbial biomass and proximity to other body sites with rich microbial environments (such as the vulva and vagina). Further research to understand these microbial communities and their relationship with urological disorders is warranted and will require careful sample collection and data analysis to draw robust and reproducible conclusions. DNA sequencing techniques enable the culture-independent identification of bacteria but have limitations such as poor taxonomic resolution, inability to distinguish between living and dead bacteria and lack of functional annotation. Despite outstanding advances in microbiome bioinformatics that have improved the information gained from 16S ribosomal RNA gene sequencing studies, adoption of these methods is still lagging.